Self-curation and artificial intelligence in the arts: a methodological proposal for artistic training - Lage, Celina F. (Farol, 2026)
In this article, I present an arts teaching methodology I developed, grounded in the use of artificial intelligence as a tool for self-curation and critical mediation within the creative process. I implemented this experience in the course "Digital Arts, Artificial Intelligence, and New Technologies Studio"—which I taught within the Graduate Program in Arts at the State University of Minas Gerais (PPGArtes/UEMG)—and subsequently adapted it for the Bachelor of Fine Arts program at the Guignard School. The proposal integrates exercises such as brainstorming, concept mapping, the use of an expanded process journal, exhibition design simulations, and career planning supported by artificial intelligence. Drawing on an account of this pedagogical experience, I discuss the approach’s impact on the training of contemporary artists, particularly regarding autonomy, awareness of one’s own poetics, and the construction of artistic trajectories.